Development of a Virtual Learning Environment Model to Fortify Life Skills for Teenage of Thailand - Songsak Haowharn,; Chaiyot Ruangsuwan, (Journal of Educational Issues, 2024)
Developing a virtual learning environment model to fortify life skills for teenagers in Thailand entails an application between information technology and communication for managing an instruction in life skills and expanding the opportunities of Thai teenagers to have access to the skills contents. The objectives of research were to develop the virtual learning environment model to fortify life skills for teenagers in Thailand. There were 4 sample groups: 176 specialists in life skills; 45 teenagers at the age of 12-18 years; 5 experts in related fields; and 9 specialists in related fields. There were 4 components of the model of virtual learning environment to fortify life skills for Thai teenagers: input, processes, output, and feedback. The model of virtual learning environment to fortify life skills for Thai teenagers gained the process and outcome was 89.66/90.90. The result indicated that the score of process of model was 89.66% and the score of product of model was 90.90%, and the efficiency index of 0.8063. The satisfaction towards virtual learning environment is fluctuating but tend to be useful for learners. This virtual learning environment model can use and employ for implementing in education.